The Wild Differences in Law when Trading in Wild Animals: a US and EU Perspective - Lubelska-Sazanów, Małgorzata (American Journal of Trade and Policy, 2018)
This paper aims to show the differences between a regular animal trade and trade in wildlife in the European Union (EU) and in the United States (USA/US). Although the ideas towards using the international sale of animals are similar in the US legal system and in the EU legal system, they have very different foundations. The European model aims for policy – neutral rules of private international law agreed on a multilateral basis, whereas the American approach uses unilateral rules of private international law based on a country’s own domestic interests. Even though there are still no binding international conflict of law rules that would apply to contracts between parties from the US and European countries, this problem could easily be solved in contract law by choosing the law applicable to the contract. However, though the conflict of law rules in the situation where one of the States of the USA is involved might be different in each case. That is the reason why the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) was drafted. Unfortunately, the conclusion based on the material presented in the article is that CITES is not effective enough. Therefore, although the law on the sale of animals leads to similar solutions in USA and in EU, even though it is based on different legal systems (common law and civil law countries), it leads to totally different solutions concerning the law on wild animals.